Olympic reform ten years later - Dichter, Heather; Kidd, Bruce (London : Routledge, 2012)
In 1999, the International Olympic Committee approved far-reaching reforms to the appointment and terms of its members, the selection of host cities for the Olympic and Winter Olympic Games, the events on the Olympic Program, and the reporting of decisions and financial information. The reforms were initiated in response to the deep crises of legitimacy it faced because of the Salt Lake City doping scandal and ongoing accusations that it turned a blind eye to doping. This book assesses the implementation and effectiveness of those reforms ten years after. It draws upon the perspectives of Olympic scholars, Olympic athletes, and IOC members, including those who were directly involved in the reform process, and makes a number of recommendations about how the process of Olympic reform could be maintained and strengthened. As such, it provides an insightful and telling report card on the modern Olympic Movement in the first decade of the 21st century, and the presidency of Jacques Rogge.
Introduction / Bruce Kidd and Heather Dichter -- Scandal and governance: inside and outside the IOC 2000 Commission / John J. MacAloon -- Athletes' rights and Olympic reform: a discussion with Johann Koss, Ann Peel and Alexandra Orlando -- Towards better Olympic accountability / Jean-Loup Chappelet -- Paradoxes and contestations of Olympism in the history of the modern Olympic Movement / Dikaia Chatziefstathiou -- From Sydney to Beijing: the evolution of the photographic coverage of Paralympic Games in five European countries / Athanasios (Sakis) Pappous, Anne Marcellini and Eric de Leseleuc -- The interpretation of environmental sustainability by the International Olympic Committee and Organizing Committees of the Olympic Games from 1994 to 2008 / Justine Paquette, Julie Stevens and Cheryl Mallen -- Community capacity and the 2010 Winter Olympic Games / Rob VanWynsberghe, Brenda Kwan and Nicolien Van Luijk -- Rules and reform: eligibility, gender differences, and the Olympic Games / Sarah Teetzel -- A research agenda for Olympic reform / Richard W. Pound.
Originally published as a special issue of Sport and society.
Includes bibliographical references and index.
Keywords: Olympics